2010
DOI: 10.1177/097215091001100208
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Offshore Outsourcing in India

Abstract: Outsourcing is an age-old practice whereas offshore outsourcing is relatively new. Issues related to offshore outsourcing came into centre stage along with the process of globalization. Offshore outsourcing of services is the result of economic and technological developments across countries. This became popular in India after the economic liberalization process. The present article makes an attempt to lay an integrative ground work for understanding outsourcing, including its evolution, theoretical developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…The benefits from globalization have direct bearing in offshore outsourcing (Agrawal, Goswami & Chatterjee, 2010), such as high value-adding activities outsourcing for innovativeness, savings on labor cost, adoption of industry best practices, and managing competitive pressures (Bertrand & Mol, 2013;Martens, Dreher, & Gaston, 2010). Factor pricing differentials result in cheaper costs of production for some activities in specific countries, giving them comparative advantage for outsourcing (Capasso et al, 2013).…”
Section: Outsourcing and Globalizationmentioning
confidence: 99%
“…The benefits from globalization have direct bearing in offshore outsourcing (Agrawal, Goswami & Chatterjee, 2010), such as high value-adding activities outsourcing for innovativeness, savings on labor cost, adoption of industry best practices, and managing competitive pressures (Bertrand & Mol, 2013;Martens, Dreher, & Gaston, 2010). Factor pricing differentials result in cheaper costs of production for some activities in specific countries, giving them comparative advantage for outsourcing (Capasso et al, 2013).…”
Section: Outsourcing and Globalizationmentioning
confidence: 99%
“…Many companies resorted to outsourcing and offshoring parts of their IT departments to locations with more favorable conditions. However, after a first wave of offshoring services especially to India (Agrawal et al, 2010), many companies became aware that geographical and cultural distance is a relevant success factor for IT offshoring projects. Therefore, they began to offshore to countries that combined a large supply of skilled IT workers at attractive labour costs and geographical as well as cultural proximity.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the phenomenon of call centres "has been tackled from many dimensions and perspectives in an attempt to explain this relatively new and different part of the world of work and employment" (Paulet 2008, p. 306). A number of issues have been scrutinised with research across a range of countries and contexts with the Indian experience among the best documented in recent writings (see Ramesh, 2004;Penter et al 2009;Agrawal et al 2010;Kuruvilla & Ranganathan, 2010;Mishra, 2011;Vira & James, 2011;Suchet, 2012;Valdyanathan, 2012;Aziz, 2013;Ghosh, 2013;Taylor et al 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This offshore call centre is an integral element of the wider expanding global business service sector or of business process outsourcing and offshoring (BPO & O) activities. Distinctions are drawn between 'captive' operations (wholly owned subsidiaries) and independent or 'third party' outsourced contractors (Agrawal et al, 2010;Sass & Fifekova, 2011). Arguably, therefore, call centres must be understood as "heterogenous organisations taking a variety of forms and offering different types of service" (Bishop et al, 2003(Bishop et al, , p. 2754.…”
Section: Literature Reviewmentioning
confidence: 99%